2023
DOI: 10.1021/acsearthspacechem.3c00203
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Formaldehyde in U.S. Oil and Gas Production Regions

Barbara Dix,
Meng Li,
Esther Roosenbrand
et al.

Abstract: We analyzed observational and model data to study the sources of formaldehyde over oil and gas production regions and to investigate how these observations may be used to constrain oil and gas volatile organic compound (VOC) emissions. The analysis of aircraft and satellite data consistently found that formaldehyde over oil and gas production regions during spring and summer is mostly formed by the photooxidation of precursor VOCs. Formaldehyde columns over the Permian Basin, one of the largest oil-and gasprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…HCHO is also underestimated over other oil producing areas in Texas and Oklahoma, specifically over the Ft. Worth and Anadarko Basins which could be due to underestimates in primary HCHO, other ROC precursor emissions, and/or secondary production. CTM simulations with WRF-Chem using the fuel-based inventory of oil and gas (FOG) (Gorchov Negron et al, 2018;Francoeur et al, 2021) showed higher HCHO VCDs over the Permian Basin than our simulations here (Dix et al, 2023). Comparisons of FOG to the 2014 NEI have shown that FOG had lower NOX emissions and higher non-methane VOC emissions (Francoeur et al, 2021).…”
Section: Tropomimentioning
confidence: 41%
See 3 more Smart Citations
“…HCHO is also underestimated over other oil producing areas in Texas and Oklahoma, specifically over the Ft. Worth and Anadarko Basins which could be due to underestimates in primary HCHO, other ROC precursor emissions, and/or secondary production. CTM simulations with WRF-Chem using the fuel-based inventory of oil and gas (FOG) (Gorchov Negron et al, 2018;Francoeur et al, 2021) showed higher HCHO VCDs over the Permian Basin than our simulations here (Dix et al, 2023). Comparisons of FOG to the 2014 NEI have shown that FOG had lower NOX emissions and higher non-methane VOC emissions (Francoeur et al, 2021).…”
Section: Tropomimentioning
confidence: 41%
“…The emissions inventory used in our simulations is based on the 2017 NEI with some updates (see EQUATES, Foley et al (2023)), and more recent versions of the NEI may show different results. Emissions of both NOX and ROC precursors will both affect HCHO production in this area (Dix et al, 2023). A sensitivity simulation in which NOX and ROC emissions from oil and gas sources were doubled resulted in increases in summer average HCHO VCD at the TROPOMI overpass time of up to 1.4×10 15 molecules cm -2 and increases of surface level 11am-3pm summer average HCHO of up to 0.5 ppb (Fig.…”
Section: Tropomimentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrent reduction of both NO x and VOC emissions would also lead to reduced HCHO production, which is important to consider in the context of O 3 given HCHO's key role as a primary radical source. A recent study concluded that over 90% of HCHO over the Permian basin results from secondary formation, and the yield of HCHO is as sensitive to NO x emissions as it is to VOC emissions (Dix et al., 2023).…”
Section: Resultsmentioning
confidence: 99%